1982
DOI: 10.1002/pol.1982.180200615
|View full text |Cite
|
Sign up to set email alerts
|

Single crystals of cellulose IVII: Influence of the cellulose molecular weight

Abstract: The influence of the degree of polymerization (DP) of cellulose was evaluated in the preparation of micron‐sized cellulose IVII lamellar crystals in order to ascertain whether a regular chain‐folded morphology could develop during their growth. For this purpose, sharp fractions of cellulose acetate were collected by preparative gel permeation chromatography. Aliquots of these fractions were deacetylated and crystallized in dilute solutions containing water, methylamine, and DMSO, and held at 150°C under pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…However, at a slightly lower precipitation temperature of 120 °C, hybrid cellulose II–cellulose IV II crystals were formed. Moreover, increasing the DPn of cellulose from 22 to 40 resulted in badly formed lamellar crystals …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, at a slightly lower precipitation temperature of 120 °C, hybrid cellulose II–cellulose IV II crystals were formed. Moreover, increasing the DPn of cellulose from 22 to 40 resulted in badly formed lamellar crystals …”
Section: Results and Discussionmentioning
confidence: 99%
“…Moreover, increasing the DPn of cellulose from 22 to 40 resulted in badly formed lamellar crystals. 38 At the end of the reaction, the contact between the dissolved low-molecular-weight cellulose chains and water under ambient conditions triggered the precipitation of the former due to a solubility differential. In addition, the higher the cellulose concentration, the more cellulose−cellulose interaction related to cellulose−solvent interactions, and the faster the precipitation occurred.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Narrow molecular weight distribution has also been found to affect the crystal morphology such that DP24 at Đ = 1.11 producing more perfect crystals . In another study, enzymatically synthesized oligocellulose with an average DP of 9 forms highly ordered cellulose II .…”
Section: Resultsmentioning
confidence: 98%
“…Narrow molecular weight distribution has also been found to affect the crystal morphology, such that DP24 at PDI = 1.11 producing more perfect crystals. 28 In another study, enzymatically synthesized oligocellulose with an average DP of 9 form highly ordered cellulose II. 29 Comparing to previous findings, this study demonstrates new pathways of interconversion between cellulose IV and II by simple solvent environment in an oligocellulose fraction with a lower DP at 7.70 and narrower polydispersity at 1.01.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, with high molecular weight, the cellulose II crystals are fibrillar in nature as they are elongated along the cellulose chain axis. Such changes in morphology, associated with a change in molecular weight, is remarkable and must certainly be connected with the impossibility for cellulose to crystallize as regular chain folded crystals (20). In an earlier study on cellulose II crystals (14), it was shown that the growth habit for low DP cellulose crystals was is the form of long flat ribbons when the crystallization conditions were optimized.…”
Section: The Resemblance Between Cellulose and Mannan Crystals Is Notmentioning
confidence: 98%